2015
DOI: 10.1590/s0100-204x2015000400004
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia para análise de adaptabilidade e estabilidade por meio de regressão quantílica

Abstract: Resumo -O objetivo deste trabalho foi desenvolver e validar uma metodologia de análise da adaptabilidade e da estabilidade fenotípica baseada em regressão quantílica (RQ). Para tanto, foram simulados valores fenotípicos com distribuição simétrica e com distribuição assimétrica à direita e à esquerda, com ou sem a presença de "outliers". A metodologia proposta foi aplicada a um conjunto de dados provenientes de um experimento com 92 genótipos de alfafa (Medicago sativa), avaliados em 20 ambientes, e comparada à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…There are methods based on analysis of variance (Plaisted & Peterson, 1959;Wricke, 1965), regression (Cruz, Torres, & Vencovsky, 1989;Eberhart & Russell, 1966;Finlay & Wilkinson, 1963;Tai, 1971;Barroso et al, 2015), nonparametric methods (Lin & Binns, 1988;Rocha, Muro-Abad, Araújo, & Cruz, 2005;Nascimento et al, 2015), linear mixed models Reml/Blup (Resende, 2004), bayesian methods (Couto et al, 2015), and artificial neural networks (Barroso et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…There are methods based on analysis of variance (Plaisted & Peterson, 1959;Wricke, 1965), regression (Cruz, Torres, & Vencovsky, 1989;Eberhart & Russell, 1966;Finlay & Wilkinson, 1963;Tai, 1971;Barroso et al, 2015), nonparametric methods (Lin & Binns, 1988;Rocha, Muro-Abad, Araújo, & Cruz, 2005;Nascimento et al, 2015), linear mixed models Reml/Blup (Resende, 2004), bayesian methods (Couto et al, 2015), and artificial neural networks (Barroso et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that the concept of adaptability used in QR models is similar to the one described by EBERHART & RUSSELL (1966); i.e., adaptability refers to the ability of cultivars to benefit from the environment. BARROSO et al, (2015) suggested that the following model of quantile regression is used in studies of adaptability and phenotypic stability:…”
Section: Methodsmentioning
confidence: 99%
“…Although interesting, such studies evaluate the adaptability in average terms, i.e., the correlation between environmental variation (X) and phenotypic response (Y) is explained by conditional expectation E(Y|X). In order to obtain information on different levels of the productivity variable, BARROSO et al (2015) proposed the use of quantile regression (KOENKER & BASSET, 1978) for adaptability and stability studies considering 92 genotypes of alfalfa (Medicago sativa L.) assessed in 20 different environmental conditions. In order to explain the functional relationship between the environmental variation (X) and the phenotypic response (Y), this method, unlike the methods based on linear regression (EBERHART & RUSSELL, 1966) provides a generalized explanation for any quantile of phenotypic values.…”
Section: Introductionmentioning
confidence: 99%
“…They differ in their biometric estimation concepts and procedures (Buitrago et al, 2011;Silva, 2012). Among these, we can mention methods that are already consolidated in the literature as those based on analysis of variance (Plaisted and Peterson, 1959;Wricke, 1965;Annicchiarico, 1992), linear regression (Finlay and Wilkinson, 1963;Eberhart and Russell, 1966;Tai, 1971;Cruz et al, 1989), methods non-parametric (Lin and Binns, 1988;Carneiro, 1998;Rocha et al, 2005), Multiple methods centroids (Nascimento et al, 2009;Nascimento et al, 2015), mixed linear models REML/Blup (Resende, 2004), Bayesian methods (Nascimento et al, 2011, Couto et al, 2015, quantile regression (Barroso et al, 2015), Artificial Neural Networks (Barroso et al, 2013), AMMI model (Gauch, 1992) and GGE biplot (Yan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%